2018
DOI: 10.1007/s40430-018-1303-5
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical investigation of the fracture behavior of adhesive shear tests single lap joints

Abstract: This work aims to establish a finite element model to simulate the behavior in cracking failure of a shear test of a single lap joint. The interest of having a satisfactory finite element model is to be able to use it to simulate the cases that have not been the subject of experimental tests. A cohesive zone model (CZM) was used to model the propagation of cracks in bonded joints, using a bilinear traction-separation law implemented in the finite element code Abaqus. The cohesive zone is represented by a row o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Subsequently, Maimí, 10 Pinho, Silvestre, 11 and Puck 12 used three-dimensional stress–strain relationships to simulate the stress solution and analyzed the failure of bolted connections in composite laminates. Apalak 8 used this method to establish an adhesive lap joint model of composite laminates and calculate stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, Maimí, 10 Pinho, Silvestre, 11 and Puck 12 used three-dimensional stress–strain relationships to simulate the stress solution and analyzed the failure of bolted connections in composite laminates. Apalak 8 used this method to establish an adhesive lap joint model of composite laminates and calculate stress.…”
Section: Introductionmentioning
confidence: 99%
“…The following research used the progressive damage analysis method to predict the failure and strength of composite structures. 8 Most studies have shown that progressive damage analysis of composite materials can be divided into the following steps: calculating the stress, setting the material failure criterion, building the damage material degradation model, and iterating the above steps until the composite material completely fails. The relevant studies are as follows:…”
Section: Introductionmentioning
confidence: 99%
“…(1), it becomes easy to calculate the steady-state ERR as shown in Eq. (15). The MCS was implemented on the response functions generated using HDMR with Pearson family of distributions.…”
Section: Hdmr-based Czmmentioning
confidence: 99%
“…From each iteration of the MCS, the particular response surface generates one set of crack length and load values to estimate the CDF of steady-state ERR using Eq. (15). The use of four statistical parameters facilitates the determination of each of the five CZM parameters in the HDMR owing to Pearson systems.…”
Section: Hdmr-based Czmmentioning
confidence: 99%
See 1 more Smart Citation